Roux‐en‐Y gastric bypass, sleeve gastrectomy, or one‐anastomosis gastric bypass? A systematic review and meta‐analysis of randomized‐controlled trials. Issue 3 (8th February 2022) - Uhe, Isabelle; Douissard, Jonathan; Podetta, Michele; Chevallay, Mickael; Toso, Christian; Jung, Minoa Karin; Meyer, Jeremy
Abstract: Objective: This study aimed to determine which bariatric procedure allows patients to obtain the best weight‐loss outcomes and a remission of type 2 diabetes. Methods: Databases were searched for randomized‐controlled trials comparing Roux‐en‐Y gastric bypass ( RYGB) with sleeve gastrectomy (SG) or one‐anastomosis gastric bypass (OAGB). The mean difference (MD) or the relative risk was determined. Results: Twenty‐five randomized‐controlled trials were analyzed. Excess weight loss (EWL, percentage) was greater for RYGB patients at 3 years (MD: 11.93, p < 0.00001) and 5 years (MD: 13.11, p = 0.0004). Higher excess BMI loss (percentage) was found in RYGB at 1 year (MD: 11.66, p = 0.01). Total weight loss (percentage) was greater for RYGB patients after 3 months (MD: 2.41, p = 0.02), 6 months (MD: 3.83, p < 0.00001), 1 year (MD: 6.35, p  < 0.00001), and 5 years (MD: 3.90, p = 0.005). No difference in terms of remission of type 2 diabetes was seen between RYGB and SG. EWL was significantly more important after OAGB than after RYGB after 1 year (MD: −10.82, p = 0.003). Conclusions: RYGB is more efficient than SG in the midterm. OAGB offers greater EWL than RYGB after 1 year, but further evidence is needed to confirm this result.